Dépossessions spatiales et négociations des mères au sein d’une cité marseillaise : pour une approche spatiale des rapports intersectionnels de pouvoir - Alice Daquin (Genre, Sexualité et Société)
This article analyses how mothers in a cité of Marseilles negotiate the daily conflict between the police and the drug trade that penetrates their living spaces. Based on ethnographic work combining interviews, observations, focus groups, and a reflexive and analytical use of drawings, I show that these mothers suffer a spatial dispossession that manifests itself in tense atmospheres, physical repressions and instrumentalizations. These mothers rely on local respectability, which is both a resource and a norm, to deploy spatial tactics of distancing, surveillance, and intervention. Through three figures – the veiled woman, the good mother and the Marseilles loudmouth – I illustrate the interweaving of ways of negotiating space and defining oneself morally in relation to a plurality of gazes. The article thus demonstrates the value of an intersectional approach to space, in order to grasp the simultaneous privileges and vulnerabilities that play out in different situations.